Musicalization Videos as a Medium for Formative Assessment to Enhance Students’ Poetry Writing Skills - Musyarofah, Musyarofah; Arfiyanti, Riskha (Deiksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
his study aims to describe the use of musicalization videos as a medium for formative assessment in poetry writing instruction for seventh-grade students at SMP Negeri 4 Kota Cirebon. Using a qualitative approach with a descriptive method, the study involved students in the creation of free-form poems, which were then developed into musicalization videos and uploaded to social media as a form of formative evaluation. The results show that this instructional strategy enhances students’ creativity, participation, and understanding of poetry. Adapting the learning process to students’ learning styles—visual, auditory, and kinesthetic—helped them express ideas, refine word choices, and integrate poetry with musical elements. Furthermore, the activity also improved students’ self-confidence, collaboration skills, and digital literacy. Thus, the use of musicalization videos as formative assessment has proven effective in developing poetry writing skills and enriching the literary learning experience in a contextual and enjoyable way.